Anti-Obesity of Dried Mulberry Fruit Powder in Mice Fed with High-Fat Diet - Chatturong, Usana; Chaiwong, Suriya; Deetud, Watcharakorn; To-on, Kittiwoot; Puntheeranurak, Supaporn; Chuleekorn, Ekarin; Chanasong, Rachanee; Kajsongkram, Tanwarat; Raksanoh, Veerada; Chinda, Kroekkiat; Nadee, Phenphechaya; Chootip, Krongkarn (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 2 (2021): April-June 2021, 2020)
Obesity is a global health problem often caused by a high-fat diet (HF). Certain natural products can prevent this, including mulberry fruit ( Morus alba L.), which has been reported to be able to reduce the body weight (BW) and contain several health benefits. However, most studies have mainly looked at the effect of plant extracts, not a natural unprocessed mulberry fruit. Therefore, the present study seeks to investigate the effect of dried mulberry fruit powder (DMP) on BW, food intake, visceral fat accumulation and liver weight and lipid in mice fed with HF. C57BL/6J mice were divided into 5 groups and fed with different diets for 3 months; i) normal diet (control), ii) HF, iii) HF+10 mg/kg DMP (HF+DMP10), iv) HF+100 mg/kg DMP (HF+DMP100) and HF+5mg/kg atorvastatin (HF+ATV5). BW, food intake, visceral fat accumulation and liver lipid including total cholesterol (TC) and triglyceride (TG) were evaluated. HF consumption significantly increased BW, food intake, visceral fat accumulation, liver weight and liver TC and TG ( P < 0.001 vs control). DMP (10 and 100 mg/kg) and atorvastatin effectively reduced BW and food intake ( P < 0.001-0.01 vs HF) and prevented visceral fat accumulation in HF-fed mice. The liver weight was found significant lower in DMP group ( P < 0.001 vs HF), but not in ATV5 group. Liver TC was reduced by treatment with DMP, both high and low dose, and atorvastatin ( P < 0.001 vs HF), while the reduction of TG was observed only in the mice treated with the high dose of DMP or atorvastatin ( P < 0.001 vs HF). In conclusion DMP, a natural unprocessed dried mulberry fruit product, possessed anti-obesity by reducing food intake and body weight. DMP also improved liver lipid profile, thus it can be developed as a food supplement for weight control and prevention against liver lipid accumulation due to HF consumption. Keywords: Morus alba , Mulberry Fruit, Obesity, Food Intake, High Fat Diet